Preventing Illegal Logging With Local Wisdom? The Guguk Forest, Merangin Jambi, Indonesia - Robi’atul Adawiyah; Dian Mukhlisa; Akhdiat Nanda Miharja (Jambe Law Journal, 2020)
This article explores the local wisdom of Guguk Village people in Merangin Regency in defending their Indigenous forests from illegal logging, committed individuals or multinational companies holding permits of Forest Concession Rights from the Government. This study aims to look at the role of the Guguk village community and their local wisdom in resolving illegal logging case in the Guguk Forest. Originally an empirical legal research, this study applied a qualitative approach in analyzing data from observation, interviews and documentation from the research. It is demonstrated that the Guguk Village community strongly hold a tradition in maintaining their traditional forest. The heads of tribes called "ninik mamak", religious leaders and community members were always involved in the efforts of preserving the Guguk forests. In addition, the administrator of the Guguk customary forest still uses a traditional process in settling illegal logging cases. The perpetrators of illegal logging will be subject to customary sanctions, where he must provide buffalo or goats as a punishment for their mistake as long as the forest exploitation is concerned. Some money has to be paid to support the village development. This method is proved to be effective in eradicating illegal logging in the Guguk forest.